Pengaruh Penggunaan Nitrogen Cair dalam Demonstrasi Edutainment Kimia terhadap Pemahaman Konsep Suhu dan Perubahan Wujud Zat - Baiq Dewi Aprilia Arnita (Journal of Science and Technology: Alpha, 2026)
Chemical edutainment demonstrations represent an engaging instructional approach to enhance students’ understanding of chemical concepts through enjoyable experimental activities. This study aims to explain the properties of liquid nitrogen and its effects on biological materials such as chicken eggs through the experiment “Sunny-Side-Up Egg Using Liquid Nitrogen.” The method employed was a practical demonstration with a descriptive observational approach. The observations revealed that liquid nitrogen, with its extremely low temperature (–196°C), can instantly freeze eggs without inducing chemical reactions, but rather through reversible physical changes. This activity enables students to comprehend the concepts of temperature, heat, and phase transitions by directly observing extreme cooling phenomena. Therefore, the use of liquid nitrogen in chemical edutainment demonstrations proves effective in increasing students’ interest and understanding of fundamental chemical concepts.